Household Sanitation Access, Maternal Personal Hygiene, and Child Snacking Practices as Predictors of Diarrheal Morbidity in Under-Five Children Living Along the Citarum River Basin - Sudasman, Fuad Hilmi; Pham , Manh Van (Journal of Health Innovation and Environmental Education, 2026)
Purpose of the study: This study aimed to examine household sanitation access, maternal personal hygiene, and child snacking practices as predictors of diarrheal morbidity among under-five children living along the Citarum River Basin, Indonesia. Methodology: A community-based case–control study was conducted in Kelurahan Andir, Baleendah Subdistrict. A total of 122 participants (61 cases and 61 controls) were selected using simple random sampling. Data were collected through structured questionnaires, non-participant observation, and environmental assessment of sanitation facilities. Variables included clean water access, latrine condition, wastewater disposal, solid waste management, maternal hygiene practices, and child snacking behaviors. Data were analyzed using descriptive and bivariate statistical approaches to assess associations between exposures and diarrheal morbidity. Main Findings: Although 75.8% of households had access to clean water meeting health standards, substantial deficiencies were observed in latrine adequacy (54.1% not meeting standards), wastewater disposal systems (59.0% inadequate), and solid waste management (67.6% inadequate). These sanitation gaps, combined with suboptimal hygiene practices and unsafe snacking behaviors, indicate multiple environmental and behavioral exposure pathways contributing to diarrheal morbidity in the study area. Novelty/Originality of this study: ffective prevention strategies should adopt an integrated environmental–behavioral approach that simultaneously strengthens sanitation infrastructure and promotes hygiene behavior change in high-risk settlements.